Herpes simplex virus infection of motor neurons: hypoglossal model. - Openshaw, H (1983)
Herpes simplex virus type 1 (HSV) was inoculated into the tongue muscle of A/J mice. Typical HSV vesicles developed on the tongue surface 4 days after HSV inoculation. Virus was isolated from hypoglossal nerve explants, and inflammatory cells appeared where the hypoglossal nerve exists from the ventral medulla. HSV viral capsids were present in astroglial cells near the point of nerve exit. A focal encephalitis ensued with immunoperoxidase staining of HSV antigens in neurons of the hypoglossal nucleus. These findings indicate that HSV can penetrate the neuromuscular junction, travel in a pure motor nerve, and produce a focal encephalitis in the corresponding central nervous system motor nucleus.